2019
DOI: 10.1155/2019/5727516
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Deriving from CAR-T Cell Treatment in Autoimmune Diseases

Abstract: Chimeric antigen receptor T (CAR-T) cells are T cells engineered to express specific synthetic antigen receptors that can recognize antigens expressed by tumor cells, which after the binding of these antigens to the receptors are eliminated, and have been adopted to treat several kinds of malignancies. Autoimmune diseases (AIDs), a class of chronic disease conditions, can be broadly separated into autoantibody-mediated and T cell-mediated diseases. Treatments for AIDs are focused on restoring immune tolerance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 75 publications
0
28
0
Order By: Relevance
“…Furthermore, new therapeutic options were established in cancer therapy using engineered T cell subsets ( 78 , 79 ). Whether these advantages are suitable for clinical application and could be transferred to chronic infections and autoinflammatory diseases is still a topic of research ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, new therapeutic options were established in cancer therapy using engineered T cell subsets ( 78 , 79 ). Whether these advantages are suitable for clinical application and could be transferred to chronic infections and autoinflammatory diseases is still a topic of research ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, for SLE, a phase I clinical trial will test the safety of CD19-CAR-T cells designed to deplete B cells (NCT03030976). In addition, CD19-CAR-T cells will be tested with or without an intracellular signaling CD137 domain ( 255 ).…”
Section: T Cell Therapymentioning
confidence: 99%
“…Applying these principles to treatment of autoimmune disorders, chimeric autoantibody receptor T (CAAR-T) cells have been developed to target autoreactive B cells secreting autoantibodies. Pre-clinical studies have found efficacy in various animal models of autoimmune disorders including autoimmune encephalomyelitis, lupus and pemphigus ( 98 ). Thus CAR T cell therapy offers a novel and attractive treatment opportunity in MG.…”
Section: Chimeric Antigen Receptor—t (Car-t) Cell Therapymentioning
confidence: 99%